The unexploited potential of data systems tracking medicines utilization: an opportunity to improve access to oncology combination therapies - Steven Simoens; David Dodwell; Michael Hartevelt; Peter Lindgren; Peter Lindgren; Michele Pistollato; Lisa Pont; Caridad Pontes; Alexander Roediger; Antun Sablek; Eric Van Ganse; Qinyi Wang; et al. (Frontiers in Pharmacology)
BackgroundWhile progress has been made in oncology treatments, including the introduction of combination therapies, barriers affect patient access. There are approaches that could improve access including combination-specific pricing that allow the price to reflect whether a product is used in monotherapy or in combination. The feasibility of this solution requires data on the utilization of combination therapies.AimTo investigate the ability of data systems across Belgium, England, France, Italy, Spain, Sweden, Switzerland and Australia to track drug utilization of combination therapies, particularly in oncology.MethodsA targeted literature review was conducted to investigate the attributes of the key data systems. One-on-one semi-structured interviews were subsequently conducted with country experts to validate the research, who were screened based on their expertise and knowledge of the respective data and reimbursement systems in their countries, followed by an advisory board to align on policy recommendations. Country-specific and cross-border insights were gathered from nine experts across these countries.ResultsThere are data systems that routinely collect medicine utilization data across seven European countries and Australia. These datasets can potentially be leveraged to track the utilization of combination therapies. Where available, administrative data systems, such as reimbursement claims data, can be leveraged, though other types of systems, such as product registries, may be more suitable in some countries, emphasizing the need to consider country-specific nuances. Using existing data systems is likely to be less resource-intensive than setting up a novel system for this application. While viable sources of data exist in most countries, many need improving to fully harness their tracking potential. There are several common areas where improvement is needed to track combination therapies effectively. These include data quality, access for different stakeholders, minimizing the burden of data entry and management, and increasing support from national authorities to foster multi-stakeholder engagement.ConclusionWhile most countries possess data systems that could serve as a foundation for tracking combination oncology therapies, these systems require optimization and proper implementation. Our core recommendation is for policymakers to explore the expansion and enhancement of data infrastructures.